MBT ROLE IN RECOVERY POSTURAL CONTROL - DANELCIUC FRANCISC TADEUS (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In our contemporary society, marked by the development of human civilization, we face more and more diseases and pain, caused by the daily lifestyle for each of us. The influence of these features of civilization are felt in the health of our legs, forced to bear the throbing rhythm within an artificial urban context. Should not surprise us the gradual atrophy and the overuse of the joints and hence the list may continue.